A systematic study of 4d and 5d transition metal mediated exchange coupling between Fe and Gd nanolaminates. (23rd October 2017) - Autieri, Carmine; Sanyal, Biplab
Abstract: We present a systematic study of the magnetic coupling between iron and gadolinium layers intermediated by 4d and 5d transition metals using density functional theory. We demonstrate that it is possible to find a magnetic coupling for most of them. In particular, for the early transition metals ( d 1, d 2, d 3 and d 4 ), a ferromagnetic coupling occurs even stronger than the 3d interlayers. Atomic size and the electronic configuration of the transition metals are crucial for the nature of the coupling. All the open shell transition metals present induced magnetic moments. By increasing the number of interlayers, an oscillating behavior in the magnetic coupling was found and the magnetic coupling goes to zero beyond four spacer layers. Using Monte Carlo simulations, we demonstrate that the interlayer strongly enhances the critical temperature in the Gd layers closest to the interface.